(untitled) (Baghdad Science Journal, 2009)
Back ground: Spectral analyses of solutions have long been applied to various body fluids for the purpose of clinical study as well as research .Human saliva can be easily obtained by non invasive .In this study typical spectra (for UV and IR) of saliva of oral cancer Squamous cell carcinoma patients were determined under average conditions and evaluated in relation to the spectra of normal specimens. Materials and Methods: Seventeen patients of oral cancer Squamous cell carcinoma and seventeen age matched healthy subject were included in this study .Chewing - Stimulated Saliva was collected in plastic test tube and stored at -20° C. Bach of saliva samples were used for UV and IR measurements. Results: Many differences between the IR spectrum of saliva of oral Squamous cell carcinoma patients and IR spectrum of normal saliva. Conclusion: The results in this study were detected that the use of IR spectroscopy may be useful in the diagnosis of oral Squamous cell carcinoma by using saliva samples.